Formation of professional competence of future teachers of geography when studying social and geographical disciplines - Бондаренко, Анжеліка Володимирівна (Pedagogy of Higher and Secondary Education, 2015)
Bondarenko O. V. Formation of professional competence of future teachers of geography when studying social and geographical disciplines. In the article the author defines the content of professional competence of future teachers of geography and its structural components (axiological, epistemological, praxеological, professional and personal, evaluative and reflexive). The potential of social and geographical disciplines in the formation of the studied phenomenon has been shown.